A Theoretical and Analytical Framework Toward Networked Communities: A Case of the Electronic Community Information Commons - Nah, Seungahn (Javnost-The Public, 2010)
The essay builds a theoretical framework toward the electronic information commons that can bridge virtually and physically networked communities. Relying on Habermas’ theory of communicative action, first, the essay maps out community as a unit of democracy in a civil society context through which it provides a meta theoretical framework to understand a conceptual framework of the electronic community information commons from such theoretical perspectives as the public sphere, social capital, and networked communities. Then, the essay proposes an analytical framework that enables scholars and researchers alike to examine how community computer networks or virtual communities contribute to physical communities and vice versa through potential research agenda and questions. Theoretical, methodological, and practical issues are discussed.